2022
DOI: 10.9778/cmajo.20210248
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of SARS-CoV-2 vaccine willingness among people incarcerated in 3 Canadian federal prisons: a cross-sectional study

Abstract: Canadian correctional settings have witnessed several large SARS-CoV-2 outbreaks since the start of the COVID-19 pandemic. [1][2][3] Many of the risk factors that predispose correctional settings to SARS-CoV-2 outbreaksclose living conditions, 4,5 an aging and comorbid population, 5,6 and limited autonomy that affects access to health care 7,8 -are nonmodifiable, underscoring the importance of SARS-CoV-2 vaccination. 9 The Canadian National Advisory Committee on Immunization prioritized residents and staff of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Prisons are therefore high-priority settings for coordinated public health responses to the COVID-19 pandemic and future outbreaks of other respiratory infections (3,(12)(13)(14)(15). However, the response to COVID-19 in prisons has been hampered due to limited access and use of personal protective equipment (PPE) in resource-limited settings, poorer access and delay the vaccination and vaccine hesitancy, security and logistical constraints, frequent movement of people between correctional settings, and the continuous entry and exit of people into the prison (16)(17)(18)(19)(20). Correctional settings, therefore, require system-level and evidence-based responses (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Prisons are therefore high-priority settings for coordinated public health responses to the COVID-19 pandemic and future outbreaks of other respiratory infections (3,(12)(13)(14)(15). However, the response to COVID-19 in prisons has been hampered due to limited access and use of personal protective equipment (PPE) in resource-limited settings, poorer access and delay the vaccination and vaccine hesitancy, security and logistical constraints, frequent movement of people between correctional settings, and the continuous entry and exit of people into the prison (16)(17)(18)(19)(20). Correctional settings, therefore, require system-level and evidence-based responses (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The first questionnaire (the pre-intervention questionnaire (Supplementary Appendix C); ∼20 minutes) assessed socio-demographic and clinical characteristics, as well as knowledge, attitudes, and beliefs towards COVID-19 vaccines. We developed the survey questions by adapting questions from the World Health Organization Strategic Advisory Group of Experts Working Group on Vaccine Hesitancy [20] , Leger’s North American Tracker – Concerns about COVID-19 [21] , Statistics Canada’s Canadian Perspectives Survey Series 3 [8] , the National Advisory Committee on Immunization Acceptability Matrix [22] , an online survey of vaccine acceptability among the Canadian general public [23] , and the 5C vaccine confidence scale [24] . We pilot-tested the questionnaire with 15 people in prison to ensure clarity before study inception.…”
Section: Methodsmentioning
confidence: 99%
“…As incarcerated individuals disproportionately experience social determinants of health associated with increased risk of COVID-19 due to a higher prevalence of chronic diseases such as hypertension and diabetes and, additionally, live in congregate settings with a high risk of transmission, efforts to maximize COVID-19 vaccine uptake, one of the most effective tools for reducing COVID-19 morbidity and mortality, are paramount. However, vaccine hesitancy is not uncommon among people in prison [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . Studies investigating reasons for vaccine refusal among people incarcerated in Canadian federal prisons found that a lack of information and misinformation were important barriers to COVID-19 vaccine acceptability [9] , [12] , underscoring the potential for educational interventions to improve COVID-19 vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by [ 56 ] using China and the US as case studies, for example, showed that acquiescence bias can inflate estimated incidence of conspiratorial beliefs and political perceptions by as much as 50%. Related to this is the dissent bias where people tend to express a negative agreement in a more frequent manner [ 57 ]. Survey results can also be affected by social desirability bias wherein respondents choose responses that they believe will make them be viewed favorably by others [ 57 ].…”
Section: Related Workmentioning
confidence: 99%